72.7k views
1 vote
Which shows the correct substitution of the values a, b, and c from the equation –2 = –x + x2 – 4 into the quadratic formula? Quadratic formula: x = StartFraction negative b plus or minus StartRoot b squared minus 4 a c EndRoot Over 2 a EndFraction

User Deeenes
by
5.5k points

2 Answers

5 votes

Answer:

i mean my guy the answer should be D then

Explanation:

User Tommybananas
by
5.3k points
0 votes

Answer:

a = 1

b = -1

c = -2

Explanation:

We reorder the equation in such way that let us see the usual

ax² + bx + c = 0

Then the original quation is:

-2 = - x + x² - 4 ⇒ 0 = 2 - x + x² - 4 ⇒ x² - x - 2 = 0

Now we are able by simply inspection to identify a, b . c comparing our equation with the general equation so :

a = 1

b = -1

c = -2

User Abhishek Jha
by
5.5k points